我如何知道我關心什麼？─不同背景大學生的自身技術之分析 How Do I Know What I Care About? -Analysis of Technologies-of-Self for Undergraduates With Different Backgrounds - 郭丁熒 Ding-Ying Guo (National Taiwan Normal University, 2016)
本研究旨在探討大學生運用自身技術之現況，並比較不同背景變項大學生的自身技術之差異情形。先根據文獻探討及40 位大學生訪談資料所編製之「大學生自身技術量表」，針對452 位大學生進行預試，再以修訂後之量表調查1,361 位大學生，調查資料經以SPSS for Windows 21.0 版套裝軟體中次數分配、單因子多變項分析、薛費事後多重比較分析法來進行資料處理與分析。研究結果發現：（一）大學生的自身技術包括鍛鍊、告解坦白、問題化、自我檢查、對話辯證、說真話、越界體驗、節制、觀察等九類，運用情形大都為中高程度；（二）大學生最常採用的自身技術是鍛鍊，而最不常採用的是告解坦白；（三）大學生採用的自身技 術因其背景之不同而呈現多樣性，其中以有宗教信仰者最為多元。本研究反映出大學生可透過自身技術來治理自我之可能性，而最常使用鍛鍊可能與大學生的學習角色有關，最不常使用告解坦白則可能與教育或文化有關。 The purposes of this study were to survey the current status of undergraduates' technologies-of-self and to analyze the differences of technologies-of-self for undergraduates with different backgrounds. The subjects were 1,361 undergraduates who participated in the survey study by using "The Technologies-of-Self Inventory for Undergraduates" as an instrument. The protocol of this instrument was prepared according to a literature review and data obtained from interviewing 40 undergraduates, whereas the validity and reliability of the instrument were established using a subsequent pretest in which 452 undergraduates participated. The data obtained from the survey study were statistically analyzed through frequency distribution, MONOVA, and a Scheffé Post Hoc Test by using SPSS for Windows 21.0 as software. The findings of this study indicate that the undergraduates adopted nine types of technologies-of-self: exercise, confession, problematization, self-examination, dialogue, parrhesia, transgressive experience, moderation, and observation. Their use of technologies-of-self was determined to be medium-high. The exercise technology was most often adopted by the undergraduates, whereas the confession technology was the most seldom used. The frequent use of exercise technology may have occurred because learning is the salient role of undergraduates, whereas the infrequent use of confession technology may have resulted from educational or cultural differences between Taiwan and Western countries. Undergraduates with a specific religious belief adopted more technologies-of-self compared with those with no specific religious beliefs. The results of this study imply that self-discovery and self-formation can be achieved by undergraduates through technologies-of-self.